2016
DOI: 10.5154/r.rchscfa.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Especies de Trichoderma del agroecosistema cacao con potencial de biocontrol sobre Moniliophthora roreri

Abstract: La monoliasis del cacao (Moniliophthora roreri) es la principal limitante parasítica de la producción de cacao (Theobroma cacao) en México. Una alternativa sostenible para el control de la enfermedad es el uso del hongo Trichoderma. El objetivo del presente estudio fue seleccionar aislamientos nativos de Trichoderma con las mejores características antagónicas y fisiológicas in vitro, para el control de M. roreri. Para ello, se caracterizaron 50 aislamientos de Trichoderma, obtenidos del agroecosistema cacao. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Parasitism and antibiosis percentage data were used to determine the potential antagonism following the formula used by Reyes-Figueroa et al [20]:…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasitism and antibiosis percentage data were used to determine the potential antagonism following the formula used by Reyes-Figueroa et al [20]:…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Several studies adopting this approach have reported the isolating several species of the genus Trichoderma that have demonstrated antagonism against M. roreri [16,17]. Generally, T. harzianum and T. virens isolates have shown high biocontrol potential against FPR [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many secondary metabolites have been reported for different culture conditions, including volatile and non-volatile compounds during the in vitro interaction of different Trichoderma species with plants and other microorganisms [ 17 , 18 , 19 ] and the improvement in the production of target compounds using genetic engineering to increase metabolite production [ 20 ]. In particular, several studies from Mexico [ 21 ], Panama [ 22 ], Peru [ 23 , 24 ], and Brazil [ 25 ] have evidenced Trichoderma–Moniliophthora interactions. In Ecuador, the antagonism of Trichoderma species from different regions has shown inhibition against banana and cocoa pathogens [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Devido às informações geradas podemos sugerir a espécie deste isolado como a mesma na qual ele foi agrupado na árvore filogenética.Trabalho semelhante foi realizado por Carvalho Filho, (2013), que ao analisar a mesma região genômica, relata que a ITS é suficiente para identificar isolados de Trichoderma spp comparando sequências depositadas no NCBI GeneBank (Corabi-Adell, 2005),. estudando a filogenia, usando a mesma região, também corrobora com resultados encontrados neste trabalho, ao identificar os isolados de Trichoderma spp tomando como suporte a região transcrita (Reyes-Figueroa et al, 2016). também conseguiu identificar em nível de espécie seus isolados de Trichoderma spp, apenas com esta região e com suporte em árvore com escore mais baixos que os encontrados neste trabalho Menezes et al (2010).…”
unclassified